Problem Sosiologis Pendidikan Islam di Indonesia, Pakistan, Arab Saudi dan Beberapa Solusi - ma'ruf ma'ruf (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2019)
This paper aims to describe the Islamic education system in Indonesia, Pakistan, Saudi Arabia, sociological issues, and alternative solutions. The method used is library research. Study results: Institutions of Islamic education in Indonesia: Islamic boarding schools, madrassas, Islamic higher education, and non-formal Islamic educational institutions. Sociological problems: misorientation, emphasis on intellectual, verbalistic and centralistic, exclusive, dichotomous, mechanical, methodological and pedagogical crises, depending on government education patterns and issues of relevance. The solution: needed concepts that clarify the basic ambivalence of philosophy, objectives, methods, and curriculum of Islamic education; reformulation of Islamic sciences; creating a more future-oriented education; institutional reconstruction; methodological innovation; fostering research enthusiasm; and integration of Islamic education with general education. Islamic education in Pakistan is divided into three: Quranic School; Mosque Primary School; and Madrasa. Sociological problems: poverty; regional disparity; gender discrimination; lack of work skills education; fund; lack of professional teachers; verbalistic; centralistic; exclusive; dichotomous; crisis methodology; and indoctrinative. Solution: increase cooperation with Islamic countries; integration of Islamic education and general education; Increasing teacher and cleric competency; Campaign for equal rights to education; and Increasing the cost of education. Islamic education in Saudi Arabia includes levels: Basic Education, Further Education: general, religious, and technical; College. Its sociological problems: the Sunni clash with the Shiites; teacher domination; gender disparity; and dichotomous problems. The solution: ijtihad ulama ’Islam across countries helps Saudi Arabia formulate an Islamic education system; and cooperation between Islamic countries.